Assessment Of The Biological Characteristics Of The Neoplastic Cells Of Ethmoid Carcinoma In Cattle - Gangadharan B (Centre of Excellence in Pathology, College of Veterinary and Animal Sciences, 1992)
Ethmoid carcinoma is an important neoplastic condition of domestic animals. Two hundred and eighty five positive cases were reported to the centre of Excellence in Pathology, during 1989 to 1991. The incidence was reported throughout the year though highest was during March (12.92 per cent) and lowest was in June and September (5.78 per cent). The report of the incidence was more from Thrissur district (21.57 per cent) compared to other districts of Kerala. Twenty – three animals were procured from various farms of the University (7) private owners, in and around Thrissur, and neighbouring districts, like Malappuram, Palakkad, Ernakulam and Kottayam (16). Histopathologically the tumours were diagnosed as Papillary adenocarcinoma (2), Adenocarcinoma (14), Squamous cell carcinoma (3), Transitional cell carcinoma (2) and Undifferentiated carcinoma (2). Efforts were made to culture ethmoid carcinoma cells in vitro, using various tissue culture media. However, the efforts were not successful in most cases. In one case RPMI – 1640 (Hi Media) with 10 per cent foetal calf serum was found to support the growth of ethmoid carcinoma cells in vitro. Histochemically GGT was demonstrated in tissue sections. There was no difference in the expression pattern of GGT in different histological types like adenocarcinoma and squamous cell carcinoma. This was considered as an indirect evidence for the involvement of a genotoxic carcinogen like aflatozin in the causation of this tumour. Special staining with luxol fast blue to demonstrate mitochondria was carried out in tumour sections. Diffuse greenish colouration of the cytoplasm of the neoplastic cells was observed indicating pronounced mitochondrial proliferation and/or damage of the mitochondria irrespective of the histological types like adenocarcinoma and squamous cell carcinoma. AgNOR count in ethmoid carcinoma was evaluated. An average count of 1.79 + 0.08 was observed in adenocarcinoma cases, whereas squamous cell carcinoma cases showed an average AgNOR count of 2.05 + 0.24. This difference was not statistically significant. Serum zinc level and copper level of sinus tumor animals was compared with that of normal animals. Tumor animals had a serum zinc level of 0.99 + 0.11 ppm, and serum copper levels was 0.86 +0.06 ppm. The serum zinc level in normal animals was 1.35 + 0.23 ppm and serum copper level was 1.04 + 0.07 ppm. Though, there was a reduction in serum zinc and copper levels in tumour animals compared to normal animals, it was not statistically significant. Parentage of six ethmoid carcinoma animals of University Livestock Farm, Mannuthy was examined. Two ethmoid carcinoma animals of the University Livestock Farm, Mannuthy had a common sire. This aspect requires further study to clarify the genetic predisposition to this condition, if any.